A interdisciplinaridade e a gamificação: as tecnologias digitais no ensino da língua espanhola no contexto da EPT - Coimbra, Renata Portela das Chagas (2023)
Over the years, Spanish language (SL) teaching has had different goals and purposes, and has been performed using different approaches and methodologies. Currently, in the context of the Federal Institute of Alagoas (Instituto Federal de Alagoas – Ifal), there is a focus on public policies oriented towards widely expanding language teaching for students and employees. There is special motivation for the proposal of meaningful Spanish teaching for students of the Integrated Middle Level Technical Course in Agroecology. The language is offered in the final year of the course curriculum. The issue driving this research arises from the challenge of performing a pedagogical practice that offers an opportunity for dialogue between the two areas of the course: the specific training area of the course curriculum (Professional Curriculum), and the Basic Curriculum, in which SL is inserted. This investigation sought to propose subsidies based on interdisciplinary pedagogical practice through the use of gamification as a teaching methodology. The epistemological and analytical basis that guided this research was historicaldialectical materialism. This research is of a qualitative nature and fulfills exploratory and descriptive purposes. The collaborative action-research method was adopted, which was developed in four phases: diagnostic research and data analysis; elaboration of the educational product (EP); application of the EP and results; adjustments and evaluation of the EP. The target audience of the research were teachers in the Basic Curriculum (propaedeutics, a curricular component of the Spanish Language) and from the Professional Curriculum (teachers in the technical area) of the course. Thematic analysis was the technique used for organizing and discussing data in the qualitative research. The results analyzed in the diagnostic phase indicated that professors are adept at the use of digital technologies and active methodologies, and that there is a lack of actions that enable dialogic praxis and the development of interdisciplinary work. The investigation demonstrated the need for continuing training to improve the use of digital technologies and gamification. To fill this gap, Spanish language teachers were proposed to create a collaborative educational product in the form of an interactive and interdisciplinary e-book. The teaching material was elaborated in a collaborative and participatory way with the SL teachers in the research location. The EP results showed that the material had a positive effect due to its organization, content and structure. Its interdisciplinary approach will enable dialogue between the different areas of the course, and it will recommended to professors of other curricular components in the Basic Curriculum.